Right of Women In The Family Law; Zakir Naik Perspective - Manaf, Abdul (Jurnal Hukum Islam, 2022)
Zakir Naik is a phenomenal muslim preacher who also gives his thoughts on women's rights. According to Zakir Naik, women actually have an equal position with men even though the implementation varies. This paper is classified as literature research with a qualitative approach. This research method is content analysis of Zakir Naik's book about women in Islam. The data was collected thematically by referring to the analysis of Zakir Naik's primary book. The results of the study concluded that women have the right to choose or accept their partners. Women also have the right to divorce their husbands if they are polygamous and it is stipulated in a marriage contract. Regarding the rights as a wife, women should not be treated as slaves who take care of housework, women must be treated properly and with respect. As a mother, a woman deserves higher respect than a fathers. In the economic realm, women may work but they are not obliged to give part of their assets to their husbands. However, women have the option to help their husbands if the husbands are unable to meet the economic needs of the family. In the realm of politics and leadership, women may serve as parliament members or government advisors, but Zakir Naik does not agree if women become presidents or prime ministers of a country